2003
DOI: 10.1063/1.1609931
|View full text |Cite
|
Sign up to set email alerts
|

Pressure As A Probe Of The Physics Of Compositionally-Substituted Quantum Paraelectrics: SrTiO3

Abstract: The influence of pressure on the dielectric properties and phase behavior was investigated for two substituted single crystals of SrTiO 3 : (a) 18 O exchanged SrTi 18 O 3 and (b) lightly doped Si^C^TiCs with x = 0.007 [SCT (0.007)]. The 18 O atoms in STO-18 reduce both the quantum fluctuations of the TiO 6 octahedra and the frequency of the soft phonon mode, leading to a ferroelectric (FE) state via a first-order transition with T c ~ 24 K at 1 bar. T c decreases very rapidly under pressure with an initial sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…At this quantum critical point, the frequency of the polar transverse optical phonon mode responsible for the ferroelectric ordering approaches zero at the Brillouin zone center (29). Recent work (33) has shown that the magnitude of the dielectric loss peak at approximately 10 K, associated with quantum critical effects (34), is linked to the quantum critical point in agreement with results from oxygen-18 substituted SrTiO3 (9). An open question in the field remains as to the quantum phase transition empirically not becoming first order as temperature is lowered and lifting the quantum criticality (35).…”
Section: Significancesupporting
confidence: 79%
See 1 more Smart Citation
“…At this quantum critical point, the frequency of the polar transverse optical phonon mode responsible for the ferroelectric ordering approaches zero at the Brillouin zone center (29). Recent work (33) has shown that the magnitude of the dielectric loss peak at approximately 10 K, associated with quantum critical effects (34), is linked to the quantum critical point in agreement with results from oxygen-18 substituted SrTiO3 (9). An open question in the field remains as to the quantum phase transition empirically not becoming first order as temperature is lowered and lifting the quantum criticality (35).…”
Section: Significancesupporting
confidence: 79%
“…Another example involves a transition from a displacive ferroelectric state to an unpolarized or quantum paraelectric state in polar materials such as the perovskite oxides (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In contrast to the case of the magnetic metals, the nature of the unpolarized state in incipient ferroelectrics remains in some respects an enigma, especially in the lowtemperature regime.…”
mentioning
confidence: 99%
“…trontium titanate is an incipient ferroelectric insulator, which can be tuned essentially continuously into the ferroelectric phase via a 'quantum' tuning parameter, such as chemical substitution, isotopic substitution or applied stress (see, e.g., refs. [1][2][3][4][5][6][7] ). The temperature-quantum tuning parameter phase diagram of SrTiO 3 and related materials has recently been discussed in terms of a phenomenological model involving the interaction of the local ferroelectric order-parameter field with itself, and with the strain field of the lattice 3,S1-S13 (see Fig.…”
mentioning
confidence: 99%
“…The normalized superconducting transition temperature, T c calculated via the model given by Eqs. (1)-(5) and the material parameters relevant to SrTiO 3 (see "Methods" section), is shown (i) vs. pressure, p, for values of n around the superconducting dome (…”
mentioning
confidence: 99%
“…An archetypical case is SrTiO 3 , in which a huge dielectric constant (e410 4 ) is observed at low temperatures (T) without showing any long-range order due to quantum fluctuations in the vicinity of a FE QCP [9][10][11] . Substituting 16 O with 18 O as well as applying external pressure have also been shown to be effective ways to control the FE transition temperature 12,13 .…”
mentioning
confidence: 99%